DESAIN KARAKTER PION BOARD GAME EDUKASI PAKAIAN ADAT DI INDONESIA - Kanaya Bintang Aulia S; Aris Sutejo; Diana Aqidatun Nisa (UNIVERSITAS STEKOM, 2025)
Abstract. Indonesia is an archipelagic country with a rich and diverse cultural heritage, reflected in its traditional clothing from various regions. However, with the advancement of time and the rapid flow of globalization, the younger generation's attention to traditional clothing has declined. A survey of youth aged 19–22 years found that most of them do not fully recognize the types, names, and origins of Indonesian traditional clothing, although they acknowledge the importance of preserving cultural heritage. To address this issue, an educational media in the form of an interactive board game was designed to reintroduce traditional clothing to young people in an engaging way. This study employed qualitative and quantitative methods, including questionnaires, interviews, observations, and focus group discussions. The board game features character pawns representing traditional attire from six major regions of Indonesia, highlighting each area's distinctive visual traits. Through this game, it is expected that youth will gain knowledge and foster a sense of love and pride in the nation's cultural heritage.